Effects of age on marathon finishing time among male amateur runners in Stockholm Marathon 1979-2014 - Niklas Lehto (Elsevier, 2016)
Purpose: The purpose of the present study was to investigate the age-related changes in the endurance performance among male amateur marathon runners. Methods: Subjects were taken from the 36 Stockholm Marathons held from 1979 through 2014, and age and finishing time were analyzed for a total of 312,342 male runners. Results: The relation was found to be a second-order polynomial, t = a + bx + cx2, which models 99.7% of the variation in the average running time t as a function of age x. The model shows that the marathon performance of the average runner improves up to age 34.3 ± 2.6 years, thereafter, the performance starts to decline. A quantification of the age's influence on running time shows that it accounts for 4.5% of the total variance seen in the performance data. Conclusion: These outcomes indicate that the effect of age on performance in endurance running events is clearly measurable, quantifiable, and possible to describe. At the same time the findings indicate that other factors, such as training, affect the performance more. A comparison with the elite showed peak performance at the same age, but the rates of change in performance with age, improvement as well as degradation, was found to be higher among the elite.